Summer-Long Grazing of High vs. Low Endophyte (Neotyphodium coenophialum)-Infected Tall Fescue by Growing Beef Steers Results in Distinct Temporal Blood Analyte Response Patterns, with Poor Correlation to Serum Prolactin Levels - Jackson, Joshua J.; Lindemann, Merlin D.; Boling, James A.; Matthews, James C. (Frontiers in Veterinary Science, 2015)
Previously, we reported the effects of fescue toxicosis on developing Angus-cross steer growth, carcass, hepatic mRNA and protein expression profiles of selected serum proteins, and blood clinical and chemical profiles, after summer-long grazing (85 d) of high (HE)- vs low (LE)-endophyte-infected fescue pastures. We now report the temporal development of acute, intermediate, and chronic responses of biochemical and clinical blood analytes determined at specified time intervals (period 1, d 0 to 36; period 2, d 37 to 58; and period 3, d 59 to 85). Throughout the trial, the alkaloid concentrations of the HE forage was consistently 19 to 25 times greater (P < 0.049) the concentration in the LE forage, and HE vs LE steers had continuously lower (P < 0.049) serum prolactin (85%), cholesterol (27%), and albumin (5%), but greater red blood cells (7%). The HE steers had decreased (P = 0.003) ADG only during period 1 (-0.05 vs 0.4 kg/d). For period 1, HE steers had reduced (P < 0.090) numbers of eosinophils (55%) and lymphocytes (18%), serum triglyceride (27%), and an albumin/globulin ratio (9%), but an increased bilirubin concentration (20%). During period 2, serum LDH activities were 18% lower (P = 0.022) for HE vs LE steers. During period 3, serum levels of ALP (32%), ALT (16%), AST (15%), creatine kinase (35%), glucose (10%), and LDH (23%) were lower (P < 0.040) for HE steers. Correlation analysis of serum prolactin and other blood analytes revealed that triglycerides (P = 0.042) and creatinine (P = 0.021) were moderately correlated (r < 0.433) with HE serum prolactin. In conclusion, three HE-induced blood analyte response patterns were identified: continually altered, initially altered and subsequently “recovered”, or altered only after long-term exposure. Blood analytes affected by length of grazing HE vs LE forages were either not, or poorly, correlated with serum prolactin. These data reveal important, temporal, data about how young cattle respond to the challenge of consuming HE pasture.